An Empirical Evaluation of the Critical Population Size for “Knowledge Spillover” Cities in China: The Significance of 10 Million - Xiaohui Gao; Qinghua Chen; Ya Zhou; Siyu Huang; Yi Shi; Xiaomeng Li (Urban Science)
In advanced countries such as the USA and China, some cities are characterized by “knowledge spillover industries”, which play crucial roles in driving innovation, entrepreneurship, and economic growth. However, the excessive expansion of megacities in China has led to the overabsorption of labour from other cities. The unchecked growth of individual megacities causes metropolitan malaise and regional imbalance, further limiting the emergence of new “knowledge spillover” cities, which is detrimental to overall economic development. This study analyses China’s employment population structure to identify the critical population size required for the formation of “knowledge spillover” cities. The results show that 10 million is the unique threshold for which cities with populations above this size see a significant improvement in the prominence of “knowledge spillover” industries. Therefore, a population base of approximately 10 million is essential for these cities to thrive. This result suggests that China should pay more attention to the construction of urban agglomerations as geographic or administrative units to better distribute resources and promote balanced regional development. This approach can help foster the emergence of more “knowledge spillover” cities, thereby enhancing national innovation capacity and economic growth.